COMPARING STIMULUS-PRESENTATION METHODS IN TEMPORAL DISCRIMINTATION TESTING. Issue 12 (15th November 2016) - McGovern, Eavan; Butler, John; Beiser, Ines; Williams, Laura; Quinlivan, Brendan; Riordan, Sean O; Reilly, Richard; Hutchinson, Michael
Abstract : Objective: To investigate any differences in temporal discrimination using two methods of stimulus presentation. Background: Temporal discrimination threshold (TDT) is a measure of the point at which an individual determines two sensory stimuli to be asynchronous (normal=30–50 ms). The classic approach involves presentation of progressively-asynchronous stimuli to an individual. The TDT is taken as the first of three consecutively-reported asynchronous stimuli. Due to the potential for a learned effect from this method of presentation, a method of constant stimuli with randomised presentation order was also employed. Methods: Ten healthy volunteers were recruited to the study. Visual and tactile TDT testing using the classic and random method of presentation was carried out in a single session. The mean TDT score was calculated for each participant. The data was fitted to a cumulative Gaussian function from which the point of subjective equality (PSE) and the just noticeable difference (JND) was calculated. Results: The mean values for the sequential method are as follows; TDT=32.03 ms, PSE=23.11 ms, JND=13.71 ms. The mean values for the random method are as follows; TDT 52.26 ms, PSE 33.35 ms, JND 28.58 ms. Conclusion: Although a difference was observed in the results between stimulus presentation, there was a trending correlation between the PSE values for the two stimulus presentation types. This suggests that while the absolute values were different, the relative values were consistent. While our study is limited by number size and future research is required, preliminary results suggest the TDT is a robust measure.